La Biographie d'un paysage Etude sur les transformations de longue durée du paysage culturel de la région de Fort-Liberté, Haïti - Sony Jean, Joseph (Sidestone Press, 2019)
This study explores long term landscape transformations of the Fort-Liberté region, Haiti. By using a landscaped biography approach, this research aims to understand the substantial developments of the region, from the Amerindian occupation, through the Spanish colonization, to the French colonial period. The study of the transformation of the landscape in the longue-durée suggests that activities of cultural groups are considered as events that were connected to each other, not just as superposed layers or isolated events. The archaeological sites dispersed in the natural environment express the idea of a complex palimpsest of the region's history. This study of the Haitian cultural landscape has proposed to take into account the multi-layered nature of the landscape in order to avoid the dichotomy between pre-colonial and colonial in this context of long-term landscape transformation.